Behavior of goats on palisade grass pasture under rotational stocking in two regrowth ages - Veloso Filho, Edivar Santos; Rodrigues, Marcônio Martins; Oliveira, Maria Elizabete; Rufino, Marcelo Oliveira Alves; Câmara, Cauê Soares; Garcez, Bruno Spíndola (Comunicata Scientiae, 2013)
This study evaluated the behavior of goats on pastures of Brachiaria brizantha cv. Marandu managedunder rotational stocking with three days of grazing and 28 and 43 days of rest. The experimentaldesign was completely randomized with two treatments and eight replications. Early pregnantAnglo-Nubian goats were used as test and control animals. The activities of grazing, idleness,movement and rumination were recorded every 15 minutes. Feeding behavior was evaluated bythe rate and depth of bites. The 43 day-rest period resulted in increased height and total productionof dry matter and leaves and lower leaf/stem ratio compared with the period of 28 days. At 28days, palisade grass showed better nutritional quality. The grazing time was not different betweentreatments. Longer times of rumination, movement and idleness were registered at 43 days. Higherbite rate was observed at 28 days of regrowth, 32.00 (bites/minute), compared with 43 days, 24.88(bites/minute). At 43 regrowth days, we observed a deeper bite 43.44 (cm). The behavior of animalsindicated that palisade grass pasture can be used between 28 and 43 regrowth days.